1708c Exposure to sub-10nm particles emitted from a biodiesel-fueled diesel engine: in vitro toxicity and inflammatory potential. (24th April 2018) - Malorni, L; Guida, V; D'Anna, A; Genovese, G; Petrarca, C; Pedata, P
Abstract : Introduction: The inflammatory effects of organic sub-10nm particles generated and emitted from a diesel engine fueled with a biodiesel and a commercial diesel oil are analysed in this paper. Diesel combustion is the major sources of ultrafine particles (UFP) in the environment, particularly in urbanised areas. In the last years, there is an increasing use of biomass-derived fuels because they are a renewable source of energy that may mitigate climate change through the reduction of net CO2 with respect to conventional fossil fuels. Although there is a general agreement on biofuels ability to reduce conventional pollutants, new and potentially harmful pollutants can be formed during biofuel combustion. In particular, the emission of sub-10nm particles is strongly increased with respect to that of larger soot particles. Methods: Organic sub-10nm particles are separated from larger sizes particulate matter by collection in water suspension for toxicological and inflammatory tests. After exposure to sub-10nm particles, the effects on proliferation, apoptosis and secretion of cytokines, chemokines and growth factors networks production is analysed in immortalised non-tumorigenic human dermal keratinocyte cell line (HaCaT) and human alveolar epithelial-like cells (A549). Results: Nanoparticles exert different cytotoxic effects in the two cell lines, suggesting that the dermal way of exposure is more sensitive than the inhalant way. These differences are most evident in the secretion of pro-inflammatory, angiogenic and proliferative cytokines and chemokines whose expression is more finely modulated in HaCaT cells compared to A-549 cells. Conclusion: Considering the size of these particles, it is important to promote the culture of prevention also for the dermal way in particularly exposed workers.